Pathways into the political arena : the perspectives of global women leaders - Rosser-Mims, Dionne; McNellis, Janet R.; Johnson-Bailey, Juanita; Egan, Chrys (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"As epitomized in our most recent Presidential election, women in politics often hit a "glass ceiling." Even though women are starting to experience more success gaining offices at state and local levels, women's participation in the political arena is still disproportionately low. This book explores current research findings, development practices, theory, and the lived experience to deliver provocative thinking that enhances leadership knowledge and improves leadership development of women around the world"--